The effects of inflation and interest rate on the stock market / Marlina Muris - Muris, Marlina (1998)
Many people mostly stock players in Malaysia believed that there is an effect of inflation and interest towards the share prices, market liquidity and market volatility. This project paper will try to determine whether there is an direct effect of inflation and interest towards stock market. The study is based on the January 1991 until May 1998. The market data use in these study are the KLSE CI The regression and chart analysis are use to determine the relationship between the inflation, interest rate and stock market. The regression analysis use by the author is to determine the coefficient of Determination (R ), t-statistic, parameter analysis and hypothesis test. The chart analysis is to determine the trend lines between the variables.